2019
DOI: 10.1016/j.bbmt.2019.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Changes before and after Hematopoietic Stem Cell Transplantation: A Systematic Review

Abstract: A B S T R A C T Severe oral problems, including oral mucositis (OM) and xerostomia, often occur after conditioning therapy for hematopoietic stem cell transplantation (HSCT). Saliva plays a major role in protecting the oral mucosa and teeth. Alterations in salivary flow rate or salivary components resulting in decreased salivary defence mechanisms may affect oral/mucosal health and may influence the severity of OM. A systematic review was conducted to assess the current scientific knowledge on changes in saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 52 publications
(83 reference statements)
2
36
5
Order By: Relevance
“…This commonly observed hyposalivation and gradual improvement of SSFR over time after HSCT is in line with previous studies and further supports the findings which have shown cytotoxic effects of chemotherapy and irradiation to damage salivary glands. Apocrine functions then regenerate gradually during years . However, in this study the SSFR of HSCT recipients with severe cGVHD did not return back to the initial level within the 24 months.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This commonly observed hyposalivation and gradual improvement of SSFR over time after HSCT is in line with previous studies and further supports the findings which have shown cytotoxic effects of chemotherapy and irradiation to damage salivary glands. Apocrine functions then regenerate gradually during years . However, in this study the SSFR of HSCT recipients with severe cGVHD did not return back to the initial level within the 24 months.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, the former studies may exaggerate the regeneration potential of salivary tissues. 16,17,27,28 Nonetheless, in our previous study, hyposalivation and persisting sicca symptoms were observed to be relatively common several years post-HSCT. 8 Hyposalivation was not associated with acute or chronic GvHD or oral manifestation of GvHD.…”
Section: Stimulated Saliva Flow Rates and Associations Of Hyposalivmentioning
confidence: 73%
See 1 more Smart Citation
“…However, current therapeutic approaches provide only limited protection. Our increasing understanding of mucositis pathophysiology, as well as the importance of shifts in salivary function, and the microbiota composition offers exciting new avenues for novel strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in saliva have been extensively described in oncologic patients, including HCT patients 7 . However, few studies have addressed the role of salivary antioxidant enzymes in the process of oral mucositis and xerostomia 8‐11 .…”
Section: Introductionmentioning
confidence: 99%